Palliative care staff perspectives: The challenges of end-of-life care on their professional practices and everyday lives - Luxardo, Natalia (2014)
This article has 3 goals: To describe the attitudes and experiences of staff on end-of-life care treatment of dying persons, to examine how the staff view their terminally ill patients, and to gather professionals' opinions on how their experiences impact their daily lives. It is a qualitative research inquiry based on a constructivist-grounded theory design. The study subjects were professionals who were part of palliative care services in Buenos Aires city during 2012. A purposive sample of 30 personnel answered an open-ended questionnaire assessing attitudes and perceptions concerning end-of-life. The results showed the following: (a) "Good" deaths were considered those in which physical symptoms were dealt with, where the patient was surrounded or on good terms with family members, and where they were at peace with themselves, any unfinished business, or God. "Bad" deaths were believed to be those where the patient was physically uncomfortable, were within a conspiracy-silence atmosphere, and died alone. (b) The factors in common that staff members identified regarding deaths were the need for spiritual comfort, peace, and acceptance and the need for attaining a deep connection with others. (c) The unexpected issues identified among end-of-life trajectories were the varying attitudes that patients had regarding death. (d) The personal life of the staff was affected by being in charge of end-of-life care decision making.